Rancang Bangun Sistem Pendeteksi Kebakaran Berbasis Internet of Things Menggunakan NodeMCU ESP8266 dan Telegram Bot - Fitri Nurlaela; Abdullah Muhajir (Kampus Akademik Publiser, 2026)
Fire is one of the disasters that can cause significant material losses and casualties if not detected at an early stage. The advancement of the Internet of Things (IoT) has enabled the development of fire detection systems capable of monitoring environmental conditions automatically and providing real-time alerts. This study aims to design and implement an IoT-based fire detection system using NodeMCU ESP8266, MQ-2 gas sensor for smoke and flammable gas detection, and a flame sensor for fire detection. The system is equipped with LED indicators and an active buzzer as local alarms, while Telegram Bot is utilized to deliver remote notifications to users. The research method consisted of requirement analysis, hardware and software design, system implementation, and functional testing conducted five times for each system component. The results indicate that the proposed system successfully performed automatic fire detection, alarm activation, and notification delivery with an average success rate of 93.33%. The MQ-2 sensor achieved a response time of 2–5 seconds, while Telegram notifications were successfully delivered in less than 3 seconds after a fire hazard was detected. These findings demonstrate that the proposed system is capable of providing effective early fire warnings and can serve as an alternative solution for improving fire safety in residential environments and small-scale buildings.